2006
DOI: 10.1167/iovs.05-1081
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of Incident Myopia in Singaporean Children

Abstract: These data provide new prospective evidence of essential links between parental myopia, IQ scores and subsequent myopia development. However, reading in books per week was not associated with incident myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(165 citation statements)
references
References 18 publications
9
153
2
1
Order By: Relevance
“…Following this review, a number of manuscripts were excluded due to information, including outcome, the exposure of interest or essential data, being omitted. A total of 16 studies were eligible for final inclusion (12)(13)(14)(15)(16)(17)(26)(27)(28)(29)(30)(31)(32)(33)(34). Of these, six were prospective cohort (12,13,15,17,31,32), eight were cross-sectional (14,16,(26)(27)(28)(29)(30)35) and two were case-control studies (33,34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this review, a number of manuscripts were excluded due to information, including outcome, the exposure of interest or essential data, being omitted. A total of 16 studies were eligible for final inclusion (12)(13)(14)(15)(16)(17)(26)(27)(28)(29)(30)(31)(32)(33)(34). Of these, six were prospective cohort (12,13,15,17,31,32), eight were cross-sectional (14,16,(26)(27)(28)(29)(30)35) and two were case-control studies (33,34).…”
Section: Methodsmentioning
confidence: 99%
“…The present meta-analysis included 16 studies with 8,393 cases of myopia. The selected studies were from four continents (seven from Asia (14,16,26,28,32,34,35), four from Europe (17,29,31,33), three from the United States (12,13,30) and two from Australia (15,27). All of the studies recruited male and female participants aged ≤31 years.…”
Section: Final Study Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no PPA segmentation was done. The Test Images were taken from Singapore Cohort study Of the Risk factors for Myopia (SCORM) [75].The same authors [77] proposed a fusion of two decision methods. Gray Level Covariance Matrix (GLCM) based texture analysis was used to generate a degree of roughness which is then compared for the temporal side and nasal side.…”
Section: Ppa Localizationmentioning
confidence: 99%
“…[22][23][24][25][26][27][28]30 Nevertheless, corneal and lens curvatures, refractive indices and retinal contour were also substantial contributors to the myopic refractive error and of importance to a comprehensive understanding of the aetiology of refractive error. 24,[26][27][28][29][30] Previous research has revealed that myopic progression is probably associated with several factors like environment, studies, lifestyle, genetics, near work [35][36][37][38][39][40][41][42][43][44][45][46] as well as with the optical defocus theory. It is now widely acknowledged that the defocus in the periphery of myopic eyes may stand a stimulus for the axial growth of the eye [17][18][19][20][21] but none has looked into the type of myopia, whether refractive or axial, at the start/detection stage and its capability to provoke eye growth.…”
Section: Introductionmentioning
confidence: 99%